The impact of strategic climate legislation: evidence from expert interviews on the UK Climate Change Act. (7th February 2021) - Averchenkova, Alina; Fankhauser, Sam; Finnegan, Jared J.
ABSTRACT: This paper assesses the importance of a strategic legal framework for action against climate change, using the UK Climate Change Act as an example. Passed in 2008, the Climate Change Act is one of the earliest and most prominent examples of framework legislation on climate change. It contains several innovative features that have since been replicated in other framework laws. We use stakeholder interviews to assess the strengths of the Act and whether it has succeeded in creating an integrated, informed and forward-looking policy process. Respondents felt that the Act had established a firm long-term framework with a clear direction of travel. However, they differed on whether the Act provided sufficient policy certainty and protection against political backsliding. Most respondents felt that the Act had changed the institutional context and the processes through which climate change is addressed. As a result, interviewees believe that the Act has helped UK climate policy to become better informed, more forward looking and better guided by statutory routines. Key policy insights A strong legal framework with statutory targets, processes and institutions can be an important tool for effective climate change governance. A broad-based framework law can make action on climate change more predictable, more structured and more evidence-based. The UK Climate Change Act is a model for such framework legislation, with important institutional features that have already been emulated in other framework laws. The main such features are statutory short-term and long-term emissions targets, a new independent advisory body (the Committee on Climate Change), clear accountability and an iterative approach to adaptation planning.